Stereoselective synthesis of chiral sultam-fused dihydropyridinones via photopromoted NHC catalyzed [4 + 2] annulation. Issue 19 (22nd August 2022) - Chen, Yangxu; Shi, Bai; Yin, Huiping; Liu, Yinping; Yu, Chenxia; Zhang, Kai; Li, Tuanjie; Yao, Changsheng
Abstract : A photopromoted NHC catalyzed asymmetric [4+2] annulation of saccharine-derived azadienes and α -diazoketones was developed, affording the corresponding sultam-fused dihydropyridinones efficiently (up to 80% yield, 99% ee and >20 : 1 d.r.). Abstract : A photopromoted NHC catalyzed asymmetric [4 + 2] annulation of saccharine-derived azadienes and α-diazoketones was developed, affording the corresponding sultam-fused dihydropyridinones in moderate to good yields with satisfactory to excellent enantio- and diastereoselectivities (up to 80% yield, 99% ee and >20 : 1 dr). This protocol features readily available substrates, mild reaction conditions and an efficient construction of vicinal tertiary and quaternary carbon stereocenters.